Reconstructive Surgery of the External Nose - Ahmad, Iftikhar; Zaman, Javed; Qayyum, Abdul; Jan, Abdullah; Shahabi, Isteraj; Ahmad, Masood (Journal of Postgraduate Medical Institute, 2011)
This is a retrospective study of reconstructive procedure used in 30 patients, who presented with various defects of nose following trauma or underwent ablative nasal surgery. They were treated between spetember, 1985 to September 1997. There were 16 male and 24 female, within the range of 15 to 65 years (average age 35 years). this reconstruction was carried out with skin grafts in 8 patietns, composite graft from auricle in 13 patients. The later group comprised of median forehead flap in 3 patients nasolabial flap in 5 patients. Converse sca;lping flap in 2 patients and combination of seagull forehead and local flaps, as described by Millard, in 3 patients. As a final step in total nasal reconstruction, costal cartilage grafts were added to lift and narrow the dorsum to make the nasal tip more pointing. After a fllow up of 6 - 18 months, over all results of repair have been satisfactory, through in few cases infection and rejection of the graft and flaps posed a few problems.